Analysis of membrane surface after the filtration of surface water containing microplastic - Edyta Kudlek; Justyna Juszczyk; Katarzyna Moraczewska-Majkut; Barbara Pieczykolan; Witold K. Nocoń (Desalination and Water Treatment)
The case study presented in this research focused on analyzing the retention of microplastic particles on commercial ultrafiltration (BX and V5) and nanofiltration (NF270) membranes. The subject of the study consists of water samples taken from a water reservoir located in the Silesian Voivodeship. Initial analysis showed the presence of microplastics at a concentration of 7–15 particles/L, but nanoplastic particles were not detected. The membrane filtration process was carried out using a stainless-steel membrane cell operated in dead-end filtration mode. The ultrafiltration was carried out at a transmembrane pressure of 0.2 MPa, while nanofiltration at 2.0 MPa. The permeate after both types of membrane filtration was free of microplastic particles. The atomic force microscope analysis of the membrane surface before and after the filtration indicated changes in the surface topography due to the fouling phenomena caused by natural matter occurring in the filtrated samples as well as microplastic pollutants. The diameters of the microplastic particles deposited on the BX and NF270 membranes were approximately 100–120 nm in height and between 900 nm and 1 µm in width. In addition, the presence of organic matter and microplastics reduces the volumetric permeate flux of both tested membranes.